How trade mark proprietors are protected against sale of counterfeit goods by third parties on online marketplaces - Kočāne, Klinta (Riga Graduate School of Law, 2019)
The internet is subject to neutral regulatory framework, and thus, over the years, has become an appealing environment for intellectual property right infringers. Namely, third parties, that abuse online marketplaces in order to distribute counterfeit goods online. Therefore, the research question is - how trade mark proprietor’s rights are enforced on online marketplaces in the European Union? The author answers this question by employing doctrinal legal research method. Sources range from various legal texts, such as directives and Regulation, to case law and additional scholarly materials. The obtained answer suggests that trade mark proprietor’s rights are not effectively exercised, as the E-Commerce Directive still includes safe harbour provisions for intermediary service providers. Further research is needed to analyse what are the possible practical and legal implications of removing safe harbour provisions from the E-commerce Directive.
Embargo 5 gadi (15.05.2019)
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Intellectual property law; Trade marks